SLANG LANGUAGE - Rafika Dewi Nasution (UIN Sumatera Utara, 2016)
This article is describe an explanation about Sociolinguistics slang is part of linguistics study, the definitions of slang, history of slang, types of slang, characteristic of slang , and kinds of slang.